Fabrication And Characterization Of Lead Free Pewter Alloys - Chou, Soklin (2011)
Lead free pewter alloys with various composition Sn-(1 3%wt)Cu and Sn-(1-3%wt)Al binary alloys and Sn-(1-3%wt)Cu-(5-7%wt)Sb ternary alloys were prepared by mixing raw materials, melting, homogenizing, and casting in a mild steel die. The alloy samples were characterized for phase identification via X-ray diffraction (XRD) analysis, and thermal behaviour via differential scanning calorimetry (DSC). Microstructures of the alloys were studied by using optical microscope (OM), field emission scanning electron microscopy (FESEM) and energy dispersive X-ray (EDX) analysis. The mechanical and physical properties of lead free pewter alloys were characterized via density test, hardness test, tensile test, castability test and surface appearance observation.